CHARACTERISTICS OF MODERN PANCREATIC INFECTION AND THEIR SIGNIFICANCE IN SUBSTANTIATING ANTIBIOTIC THERAPY IN ACUTE PANCREATITIS - Andryuschenko, V.P.; Andryushchenko, D.V.; Mahlovanyi, V.A. (World of Medicine and Biology, 2019)
Acute pancreatitis (AP) is one of the most topical problems of urgent abdominal surgery. The modern approach to its solution lies in the elaboration of the multidisciplinary principle of therapeutic tactics, which reflects the general tendency of medicine in relation to the integration and mutual influence of various specialties in the study of complex biological objects. One of the priority components of this approach to AP is to find out the characteristics of modern pancreatic infection (PI) with assessment of its clinical significance to address the priority issues of therapeutic tactics and, in particular, the feasibility and optimal regimens for assignment of antibacterial drugs - antibiotics in the treatment of patients [5 , 7,10,13]. Therefore, the need to address this problem becomes increasingly important. The purpose of the present work was to find out the features of modern PI with an in-depth analysis of its main characteristics and to assess the significance of the results obtained in order to substantiate the antibiotic therapy regimen in AP. The performed microbiological studies provided grounds to state that PI was represented by a wide spectrum of microflora with an aerobic (55%) and anaerobic (45%) type of metabolism. The species composition of bacteria consisted mainly of enterobacteria (66%) in the form of Escherichia coli, Enterobacter aerogenes, Klebsiella pneumoniae, Pseudomonas aerogenosa and anaerobic non-clostridial microflora with dominant bacteria genus Bacteroides (23%), Peptostreptococcus spp. (20%). , Staphylococcus saccharoliticus (18%). In order to find out the characteristics of modern pancreatic infection at 44 patients with acute pancreatitis at the first stage of the work 147 bacteriological studies were performed on the material - the content of peripancreatsc fluid and fragments of necrotic tissue of the pancreas and retroperitoneal tissue. It was stated that pancreatic infection was represented by a microflora with dominance of aerobic bacteria in the form of monoculture (37%) and aerobic-anaerobic associations (39%) with gram negative charater (56%), different pathogenicity of bacteria to pathomorphological substrates and invariability of existing associations in 57 % of patients. Sensitivity of pancreatic infection to different groups of antibiotics is established. On the second stage of the study, 460 patients with acute pancreatitis evaluated the efficacy and determined the feasibility of implementing various regimens of antibiotic therapy, in particular preventive, which contributed to the preservation of aseptic inflammatory process in 68% of observations and etiotropic - with the indigenous polyresistance microflora.